2017
DOI: 10.1155/2017/7132941
|View full text |Cite
|
Sign up to set email alerts
|

Candidate Gene Identification of Feed Efficiency and Coat Color Traits in a C57BL/6J × Kunming F2 Mice Population Using Genome-Wide Association Study

Abstract: Feed efficiency (FE) is a very important trait in livestock industry. Identification of the candidate genes could be of benefit for the improvement of FE trait. Mouse is used as the model for many studies in mammals. In this study, the candidate genes related to FE and coat color were identified using C57BL/6J (C57) × Kunming (KM) F2 mouse population. GWAS results showed that 61 and 2 SNPs were genome-wise suggestive significantly associated with feed conversion ratio (FCR) and feed intake (FI) traits, respect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…A previous study reported that TYR showed the greatest level of differential expression in the skin of black versus white chickens [24]. In humans [25][26][27] and mice [28], several genome-wide studies have also shown signals of association for skin or coat color in the genomic regions encompassing the GRM5 and TYR genes. On GGA1, there were three other significant markers close to the RAB38 gene whose products is a Ras-related protein.…”
Section: Discussionmentioning
confidence: 96%
“…A previous study reported that TYR showed the greatest level of differential expression in the skin of black versus white chickens [24]. In humans [25][26][27] and mice [28], several genome-wide studies have also shown signals of association for skin or coat color in the genomic regions encompassing the GRM5 and TYR genes. On GGA1, there were three other significant markers close to the RAB38 gene whose products is a Ras-related protein.…”
Section: Discussionmentioning
confidence: 96%
“…However, there was no clear signal associated with the hernia even when the cutoff P value was < 0.05. In consideration of different statistical models that tend to perform differently from various datasets [40], a case-control model implemented in PLINK, which has been previously reported [41], was employed to ascertain the remarkable SNPs associated with inguinal/scrotal hernias, and 7 significant association loci and 2 candidate genes (CPNE5, MAP7D2) were identified. Some studies have reported that case-control analysis by PLINK controlled the population structure and kinship among individuals as covariates to reduce false positives, but the use of covariates and testing markers may cause confounding, which could produce false negatives [42].…”
Section: Discussionmentioning
confidence: 99%
“…Genes suspected to be associated to feed efficiency were extracted, including the Fto gene which is known to be related to obesity (e.g., Church et al, 2009), Stat6 gene which is thought to be related to lipid production (e.g., Ricardo‐Gonzalez et al, 2010) and Phospho1 gene encoding enzyme possibly regulating thermogenesis, insulin resistance and obesity (e.g., Jiang, Chavarria, Yuan, Lodish, & Huang, 2020; Suchacki et al, 2020). Genes previously reported as candidate causal ones for feed efficiency and related traits were also included, such as Etv4 (e.g., Brunes et al, 2021; Weber et al, 2016), Fgd6 (e.g., Ghoreishifar et al, 2020), Fgf10 (e.g., Miao et al, 2017), Ghs r (e.g., Jin et al, 2014) and Igf2bp1 genes (e.g., Chen et al, 2019; Liu, Xu, Lan, Cao, & Pan, 2021). These findings might support the difference in chemical components, feed efficiency and MER between the lines reported by Darhan et al (2017).…”
Section: Resultsmentioning
confidence: 99%